A novel, potent dual inhibitor of Arg‐gingipains and Lys‐gingipain as a promising agent for periodontal disease therapy. Issue 8 (28th April 2014) - Kataoka, Shinsuke; Baba, Atsuyo; Suda, Yoshimitsu; Takii, Ryosuke; Hashimoto, Munetaka; Kawakubo, Tomoyo; Asao, Tetsuji; Kadowaki, Tomoko; Yamamoto, Kenji
Abstract : The periodontal pathogen Porphyromonas gingivalis produces a unique class of cysteine proteinases termed gingipains that comprises Arg‐gingipain (Rgp) and Lys‐gingipain (Kgp). Growing evidence indicates that these 2 types of gingipains synergistically contribute to the entire virulence of the organism and increase the risk of periodontal disease (PD) by disrupting the host immune system and degrading the host tissue and plasma proteins. Therefore, a dual inhibitor of both gingipains would have attractive clinical potential for PD therapy. In this study, a novel, potent, dual inhibitor of Rgp and Kgp was developed through structure‐based drug design, and its biological potency was evaluated in vitro and in vivo. This inhibitor had low nanomolar inhibitory potency ( K i =40 nM for Rgp, K i =0.27 nM for Kgp) and good selectivity for host proteases and exhibited potent antibacterial activity against P. gingivalis by abrogating its manifold pathophysiological functions. The therapeutic potential of this inhibitor in vivo was also verified by suppressing the vascular permeability that was enhanced in guinea pigs by the organism and the gingival inflammation in beagle dog PD models. These findings suggest that a dual inhibitor of Rgp and Kgp would exhibit noteworthy anti‐inflammatory activity in the treatment of PD.—Kataoka, S., Baba, A., Suda, Y., Takii, R., Hashimoto, M., Kawakubo, T., Asao, T., Kadowaki, T., Yamamoto, K. A novel, potent dual inhibitor of Arg‐gingipains and Lys‐gingipain as a promising agent for periodontal disease therapy. FASEB J. 28, 3564–3578 (2014). www.fasebj.org